Growth Performance, Feed Efficiency and Feed Cost per Gain of Juvenile Redclaw Crayfish Cherax quadricarinatus Fed Different Commercial Diets - Hendriana, Andri; Haifa, Aliya Nurul; Ekasari, Julie; Taufiqulloh; Wahyudi, Imam Tri (College of Vocational Studies, Bogor Agricultural University, 2024)
Aquaculture production is greatly influenced by species growth, feed efficiency, and feed costs. This study aims to evaluate different commercial diets on growth performance, feed efficiency, and feed cost per gain of juveniles redclaw crayfish Cherax quadricarinatus. The study used three treatments triplicate, consisting of Diet A (commercial diet with crude protein 40%), Diet B (commercial diet with crude protein 41%), and Diet C (commercial diet with crude protein 41%). The initial crayfish, with sizes of 0,24 ± 0,03 g and 2,1 ± 0,1 cm, were stocked in nine glass tanks (100 cm × 40 cm × 40 cm) with a stocking density of 50 crayfish m-2 for 60 days. The crayfish were fed twice daily at 07.00 and 17.00 WIB under a restricted feeding rate of 3% of biomass. The result shows that the final weight, average daily growth, specific growth rate feed conversion ratio, protein retention, and protein efficiency ratio did not differ in each treatment (P>0,05). Besides, the feed cost per gain (FCG) showed that diet B and diet C were better than diet A (P<0,05), with values ​​of IDR 27,679±2,378 kg-1 and IDR 26,579±2,624 kg-1, respectively, which means those treatments having better economic value. So, This study concluded that commercial diet C is recommended as feed for redclaw crayfish because it is more economical.